(untitled) (International Seven Journal of Health Research, 2024)
The aim is to reflect on the ongoing impact of vaccination on society’s quality of life. In the light of the third central concept of Dorothea Orem’s Self-Care Theory, which deals with the nursing system, the aim is to analyze the role of the nursing team in promoting self-care through vaccination, highlighting its significant influence in promoting public health. This is a reflective, descriptive and critical study, carried out after a search of current scientific literature using as a source scientific journals indexed in Google Scholar, PubMed and databases grouped and indexed in the Virtual Health Library. The nursing team plays a vital role in promoting vaccination-related self-care. This involves empowering individuals to make informed decisions about their health, including the decision to get vaccinated, understanding the vaccination schedule and keeping up-to-date vaccination records. The nursing team is therefore recognized as a key player in ensuring the effectiveness of vaccination campaigns, especially in a scenario of rapid dissemination of information and growing challenges in the acceptance of vaccines, directly impacting on society’s quality of life in the context of the immunization process.